The evolving landscape of prostate cancer stem cell: Therapeutic implications and future challenges - Eun-Jin Yun; U-Ging Lo; Jer-Tsong Hsieh (Asian Journal of Urology)
Prostate cancer (PCa) is the most common cause of malignancy in males and the second leading cause of cancer mortality in United States. Current treatments for PCa include surgery, radiotherapy, and androgen-deprivation therapy. Eventually, PCa relapses to an advanced castration-resistant PCa (CRPC) that becomes a systematic disease and incurable. Therefore, identifying cellular components and molecular mechanisms that drive aggressive PCa at early stage is critical for disease prognosis and therapeutic intervention. One potential strategy for aggressive PCa is to target cancer stem cells (CSCs) that are identified by several unique characteristics such as immortal, self-renewal, and pluripotency. Also, CSC is believed to be a major factor contributing to resistance to radiotherapy and conventional chemotherapies. Moreover, CSCs are thought to be the critical cause of metastasis, tumor recurrence and cancer-related death of multiple cancer types, including PCa. In this review, we discuss recent progress made in understanding prostate cancer stem cells (PCSCs). We focus on the therapeutic strategies aimed at targeting specific surface markers of CSCs, the key signaling pathways in the maintenance of self-renewal capacity of CSCs, ATP-binding cassette (ABC) transporters that mediate the drug-resistance of CSCs, dysregulated microRNAs expression profiles in CSCs, and immunotherapeutic strategies developed against PCSCs surface markers. Keywords: Prostate cancer, Cancer stem cell, Normal stem cell